The Identification of Fungus Among Meat Sellers' Toes with Tinea Pedis at Terminal 42 Traditional Market Gorontalo City - Ismail Mukusibu; Yolan Dunggio; Mindy Eka Astuti (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to identify the presence of fungus among meat sellers' toes with Tinea pedis at Terminal 42 traditional market, Gorontalo City. The type of research used in this research is descriptive observational with a qualitative approach, The sample in this study is a total of meat sellers who work in the Terminal 42 Market of Gorontalo City, which are 15 samples The sampling technique used is the total sampling technique. As well as using interview data collection techniques and examination of fungal culture. Data analyzed a sort of descriptive set is describing the morphology fungi dermatofita based on observations of macroscopic and microscopic and continued with both the identification of identifying with matching characteristic of fungi obtained from our observation with reference to the identification The results show that based on macroscopic and microscopic examination of the toes of a butcher with Tinea pedis at Terminal 42 traditional market, Gorontalo City. Trichophyton rubrum was found, which is a dermatophyte group. Moreover, Aspergillus sp, Rhizopus sp, Candida albicans, and Metarhizium anisopliea species were also found, namely non-dermatophyte fungi.